Apigenin inhibits endothelial-to-mesenchymal transition of coronary artery endothelial cells and myocardial fibrosis by regulating ribosome biogenesis through GTPBP4 modulation - Xiaoyong Hu; Zhaoying Yang; Rui Tang; Zhongying Lv; Ting Zou; Yuanyuan Dou; Hongjian Li (Human Cell, 2025)

LncRNA OLMALINC promotes osteosarcoma progression through USP1-mediated autophagy suppression - Jianping Li; Bo Yu; Zhaowen Xue; Yiping Liang; Shanchuang Chen; Tao Gui; Zitao Liu; Lei Zhang; Rui Peng (Human Cell, 2025)

Nanofiber-based delivery of evodiamine impedes malignant properties of intrahepatic cholangiocarcinoma cells by targeting HDAC4 and restoring TPM1 transcription - Rui Zou; Yiyao Wang; Yaoqing Cai; Zhenming Xing; Yongfu Shao; Duo Li; Chunchun Qi (Human Cell, 2024)

EphA1 aggravates neuropathic pain by activating CXCR4/RhoA/ROCK2 pathway in mice - Qi Li; Rui Li; Xiaoxi Zhu; Xiaolei Chu; Xiaoqiong An; Ming Chen; Lei Zhang; Mingwei Gao; Long Chen (Human Cell, 2023)

TEAD4 predicts poor prognosis and transcriptionally targets PLAGL2 in serous ovarian cancer - Xin Tong; Yi-Si Liu; Rui Tong; Wei-Wei Tang; Xue-Mei Li; Chun-Yan Wang; Yong-Peng Wang (Human Cell, 2023)

Bone marrow mesenchymal stem cells derived exosomal Lnc TUG1 promotes bone fracture recovery via miR-22-5p/Anxa8 axis - Wei Li; Lihong Li; Rui Cui; Xiaoqing Chen; Haifeng Hu; Yuyu Qiu (Human Cell, 2023)
Bone fracture healing is a complex physiologic process that involves changes in the expression of several thousand genes. Long noncoding RNAs (lncRNAs) may have critical biological roles in this process. The objectives of the present study were to determine whether BMSC-derived exosomal lncTUG1 can enhance osteogenic differentiation and thereby promoting bone fracture recovery and to investigate its potential mechanisms of action. Bone marrow mesenchymal stromal cells were isolated from mice and cultured for the following experiments. After adipogenic and osteogenic differentiation induction, Oil Red O, alizarin red S, and alkaline phosphatase staining solutions were applied to confirm the formation of lipid droplets and calcium nodules. Western blotting analyses, real-time reverse transcription PCR assays, luciferase reporter were performed to confirm relative RNA and protein expressions and luciferase activities of transfected cells. RNA pull-down and RNA immunoprecipitation assays were also carried to verify the interaction between lncTUG1 and miR-22-5p. Additionally, a mouse model of closed femoral fractures was generated to evaluate the in vivo effect of increased lncTUG1 on fracture healing. BMSC-derived exosomal lncTUG1 enhanced the activity of osteoblasts. Overexpression of miR-22-5p reversed the osteopromoting effect of increased lncTUG1. The knockdown of Anxa8 reversed the osteogenic effect of miR-22-5p inhibitors, indicating an interaction between Anxa8 and miR-22-5p. Upregulation of lncTUG1 could promote the fracture recovery in vivo. In conclusion, the present study highlights the functional importance of BMSC-derived exosomal lncTUG1 in the process of bone fracture recovery.

Establishment and comprehensive analysis of a new human cell line (NK-NJ) with NK-cell characteristics established from extranodal natural killer cell lymphoma/leukemia - Jin-Hua Liang; Wei-Ting Wang; Kai-Xin Du; Tong-Yao Xing; Yan Wang; Hui Wang; Lu Liu; Rui Guo; Yang Shao; Junheng Liang; Yue Li; Hao-Rui Shen; et al. (Human Cell, 2022)

Hedgehog pathway is negatively regulated during the development of Drosophila melanogaster PheRS-m (Drosophila homologs gene of human FARS2) mutants - Lidangzhi Mo; Rui Li; Chunxia He; Qi Chen; Changwei Xu; Liangliang Shen; Kun Chen; Yuanming Wu (Human Cell, 2022)

RIG-I acts as a tumor suppressor in melanoma via regulating the activation of the MKK/p38MAPK signaling pathway - Rui Guo; Shun-Yuan Lu; Jin-Xia Ma; Qian-Lan Wang; Lu Zhang; Ling-Yun Tang; Yan Shen; Chun-Ling Shen; Jin-Jin Wang; Li-Ming Lu; Zhu-Gang Wang; Hong-Xin Zhang (Human Cell, 2022)
Studies have indicated that RIG-I may act as a tumor suppressor and participate in the tumorigenesis of some malignant diseases. However, RIG-I induces distinct cellular responses via different downstream signaling pathways depending on the cell type. To investigate the biological function and underlying molecular mechanism of RIG-I in the tumorigenesis of melanoma, we constructed RIG-I knockout, RIG-I -overexpressing B16-F10 and RIG-I knockdown A375 melanoma cell lines, and analyzed the RIG-I-mediated change in the biological behavior of tumor cells in spontaneous and poly (I:C)-induced RIG-I activation. Cell proliferation, cell cycling, apoptosis and migration were detected by CCK-8 assay, BrdU incorporation assay, Annexin V–PI staining assay and Transwell assay, respectively. In vivo tumorigenicity was evaluated by tumor xenograft growth in nude mice and subsequently by Ki67 staining and TUNEL assays. Furthermore, Western blotting was utilized to explore the underlying mechanism of RIG-I in melanoma cells. Our data showed that RIG-I promotes apoptosis and inhibits proliferation by G1 phase cell cycle arrest in the melanoma cell lines. Mechanistically, RIG-I induced the phosphorylation of p38 MAPK and MAPK kinases MKK3 and MKK4. In conclusion, the current study demonstrated that RIG-I suppressed the development of melanoma by regulating the activity of the MKK/p38 MAPK signaling pathway, which is relevant to research on novel therapeutic targets for this malignant disease.

Long noncoding RNA MIR3142HG accelerates lipopolysaccharide-induced acute lung injury via miR-95-5p/JAK2 axis - Yanqiu Gao; Shuangfeng Li; Rui Dong; Xiaoyan Li (Human Cell, 2022)

Hirsutella sinensis inhibits NLRP3 inflammasome activation to block aristolochic acid-induced renal tubular epithelial cell transdifferentiation - Min Yu; Yu-lin Man; Meng-hua Chen; Li-hua Wu; Yi Zhou; Xiao-ling Zhou; Na Chen; Rui Ma; Li-na Sun (Human Cell, 2020)

Erratum to: Glycogen synthase kinase 3 (GSK3)-inhibitor SB216763 promotes the conversion of human umbilical cord mesenchymal stem cells into neural precursors in adherent culture - Liyang Gao; Mingyan Zhao; Peng Li; Junchao Kong; Zhijun Liu; Yonghua Chen; Rui Huang; Jiaqi Chu; Juanhua Quan; Rong Zeng (Human Cell, 2017)

Glycogen synthase kinase 3 (GSK3)-inhibitor SB216763 promotes the conversion of human umbilical cord mesenchymal stem cells into neural precursors in adherent culture - Liyang Gao; Mingyan Zhao; Peng Li; Junchao Kong; Zhijun Liu; Yonghua Chen; Rui Huang; Jiaqi Chu; Juanhua Quan; Rong Zeng (Human Cell, 2017)